Physiological response of palm seeds to accelerated aging - Negreiros, Gisele de Freitas; de Andrade Perez, Sonia Cristina Juliano Gualtieri (Pesquisa Agropecuaria Brasileira, 2004)
The aim of this work was to evaluate the differences in seed physiological quality of four Palmae species submitted to accelerated aging. After harvest, the seeds of each species were exposed to accelerated aging (45ºC and 100% R.U.) during 0 (control), 12, 24, 36 and 48 hours. Euterpe edulis and Dypsis lutescens were sensible to accelerated aging and germination process was inhibited after 12 hours inside the camara. Roystonea oleracea and Phoenix reclinata were more tolerant than the other species, but exibited gradual decrease on seed vigor, as the time inside the camara increased. The critical period for some vigor parameters evaluated was 48 hours inside the camara.